Al Microheater and Ni Temperature Sensor Set based-on Photolithography with Closed-Loop Control - Pittaya Deekla; Rungrueang Phatthanakun; Sarawut Sujitjorn; Nimit Chomnawang (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This article proposes the development of a new low-cost microheater and temperature sensor set. It was developed based on Micro-Electro-Mechanical Systems (MEMS) which based on photolithography technique and lift-off technique. Thin film of aluminum was utilized as microheater and encompassed nickel temperature sensor inside in order to decrease response time of the desired temperature. To control the various temperatures correctly, closed-loop feedback control based on PI-controller was adapted into control circuit system. Microcontroller was implemented to control and observe the responses of temperature between 40°C and 120°C. Simulation and experimental results are also presented.